The New Brazilian Anti-Corruption Law - Carlos Moura (Journal of Economics Library, 2015)
This piece is intended to call the attention of directors, businessmen and company managers to a fact of great relevance. With the enactment of Law 12,846/13, its first and second articles imposed the accountability, administrative and civil liability of legal entities when of the perpetration of acts against the domestic or foreign Public Administration, meaning a relevant risk as the companies will liable regardless of guilt in the practice of corruption committed in its own interest or benefit.
Keywords: A10; 330; anti-corruption; companies